KARAKTERISASI Bacillus spp. DAN Fusarium sp. DARI TANAMAN LADA (Piper nigrum L.) DI DESA JAGA - Flori, Florianus; Mukarlina, Mukarlina; Rahmawati, Rahmawati (Jurnal Protobiont, 2020)
Pepper (Piper nigrum L.) is one of the farm crop which become commodities in West Kalimantan. This research aimed to determine the morphological characteristic of Bacillus bacteria from rhizosphere of pepper and Fusarium fungi with symptoms of yellow disease. Sampling was done in pepper farm crops, Sungai Jaga Village, Bengkayang Regency. Isolation and identification were implemented at Microbiology Laboratory, Department of Biology, Faculty of Mathematics and Natural Science, Tanjungpura University, Pontianak. The result of isolation and identification showed 4 bacterial isolates belong to genus Bacillus, namely Bacillus sp. BRF1, Bacillus sp. BRF2, Bacillus sp. BRF3 and Bacillus sp. BRF4 and one isolate of Fusarium sp. JDF from pepper with symptom of yellow desease.